2015
DOI: 10.1309/ajcpm8rj2ecawogq
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Pathologic Factors to Efficacy of Sorafenib Treatment in Patients With Metastatic Clear Cell Renal Cell Carcinoma

Abstract: As a novel histologic prognostic parameter, growth pattern may be useful for predicting response to sorafenib treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…In addition to a primary tumor size >7 cm, other significant factors determining survival among the 177 patients were clinical T3-4 stage (for PFS and OS), collecting system invasion (for OS), and tumor necrosis (for OS) within the primary renal tumor. These data corresponded to previous studies of invasive and advanced RCC, where clinical T3-4 stage, aggressive characteristics such as collecting system invasion [ 18 , 19 ], and faster growth rates with tumor necrosis [ 20 22 ] reflected advanced disease states with a negative impact on survival. However, none of these previous reports included TT agent-treated mRCC patients; this is the first study to show that certain primary tumor-related factors were significant indicators of prognosis in TT agent-treated mRCC patients, particularly those receiving sorafenib.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition to a primary tumor size >7 cm, other significant factors determining survival among the 177 patients were clinical T3-4 stage (for PFS and OS), collecting system invasion (for OS), and tumor necrosis (for OS) within the primary renal tumor. These data corresponded to previous studies of invasive and advanced RCC, where clinical T3-4 stage, aggressive characteristics such as collecting system invasion [ 18 , 19 ], and faster growth rates with tumor necrosis [ 20 22 ] reflected advanced disease states with a negative impact on survival. However, none of these previous reports included TT agent-treated mRCC patients; this is the first study to show that certain primary tumor-related factors were significant indicators of prognosis in TT agent-treated mRCC patients, particularly those receiving sorafenib.…”
Section: Discussionsupporting
confidence: 89%
“…A greater primary tumor size with smaller necrotic areas, the absence of lymphovascular and collecting system invasion within the primary tumor, and less metastatic lesions without bone involvement are expected to reflect better prognosis with sorafenib treatment, whether before or after nephrectomy or metastasectomy [ 15 , 27 , 28 ]. Additionally, Araki et al emphasized the importance of primary tumor characteristics, especially tumor growth patterns, and also found that the Fuhrman nuclear grade, presence of a sarcomatoid component, lymphovascular invasion, tumor necrosis, growth pattern, and other pathological parameters of the primary tumor were potentially useful prognostic indicators, as they could be assessed easily at the time of nephrectomy [ 22 ]. The importance of primary tumor characteristics and disease extent in this study was noteworthy because sorafenib is considered systemically less potent than other similarly acting tyrosine kinase inhibitors, although with more tolerability, fewer dose reductions, and/or less severe adverse events [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are four types of renal carcinoma: clear cell renal carcinoma, granulosa cell renal carcinoma, mixed cell renal carcinoma, and undifferentiated cell renal carcinoma. 18 Among them, the vast majority are renal clear cell carcinoma, accounting for 70%~80% of renal carcinoma. 19,20 Renal clear cell carcinoma is often asymptomatic in the early stage, or only fever, fatigue and other systemic symptoms; tumor volume was found to increase.…”
Section: Discussionmentioning
confidence: 99%